Effect of clamping pressure on interfacial fusion morphology and fracture mechanism of CFRTP/Ti6Al4V laser bonding joint featuring blind hole surface microtextures. (September 2022) - Wang, Feiyun; Zhang, Pingze; Bu, Hengchang; Chen, Weiwen; Li, Binbin; Zhan, Xiaohong
Highlights: Focusing on the effect of clamping pressure on interfacial fusion morphology and mechanical property of CFRTP/Ti alloy laser bonding joint. Increasing clamping pressure is beneficial to the material diffusion behavior at the joining interface. Fracture mechanisms of joints under various clamping pressure are discussed based on fusion characteristics and fracture surface morphology. Abstract: Carbon fiber reinforced thermoplastic composites (CFRTP) and titanium (Ti) alloy are both important lightweight materials in aircraft and aerospace applications, whose heterogeneous hybrid structure manufactured by laser joining technology is propitious to leverage the performance advantages of each component. The clamping pressure during the laser joining procedure is one of the most critical process parameters affecting the joint performance. Laser joining of CFRTP to Ti alloy (Ti6Al4V) under various clamping pressure is carried out, aimed to investigate the effect of clamping pressure on interfacial fusion morphology, mechanical property and fracture mechanism of bonding joint featuring blind hole surface microtextures. The fusion morphology and element distribution at joining interface are observed by scanning electron microscope (SEM) and energy dispersive spectrometer (EDS). Moreover, the fracture morphology and fracture mechanism are analyzed after tensile-shear test. The results show that an appropriate increase of clamping pressure improves the filling effect of melted resin to microtextures on Ti alloy surface, while too high pressure is inclined to induce the generation of pores and cracks at the joining interface. The fracture load of the joints increases and then decreases as the pressure rises, and it reaches a peak value of 3821.4 N corresponding to the optimal interfacial fusion effect when the pressure is 0.8 MPa. Significant distinctions exist in the main fracture mechanisms under different clamping pressure conditions, which lead to different fracture surface morphologies and mechanical performance of laser bonding joints.